3D Porous Oxidation‐Resistant MXene/Graphene Architectures Induced by In Situ Zinc Template toward High‐Performance Supercapacitors. (12th March 2021) - Yang, Xue; Wang, Qian; Zhu, Kai; Ye, Ke; Wang, Guiling; Cao, Dianxue; Yan, Jun
Abstract: 2D MXene materials have attracted intensive attention in energy storage application. However, MXene usually undergoes serious face‐to‐face restacking and inferior stability, significantly preventing its further commercial application. Herein, to suppress the oxidation and self‐restacking of MXene, an efficient and fast self‐assembly route to prepare a 3D porous oxidation‐resistant MXene/graphene (PMG) composite with the assistance of an in situ sacrificial metallic zinc template is demonstrated. The self‐assembled 3D porous architecture can effectively prevent the oxidation of MXene layers with no evident variation in electrical conductivity in air at room temperature after two months, guaranteeing outstanding electrical conductivity and abundant electrochemical active sites accessible to electrolyte ions. Consequently, the PMG‐5 electrode possesses a striking specific capacitance of 393 F g −1, superb rate performance (32.7% at 10 V s −1 ), and outstanding cycling stability. Furthermore, the as‐assembled asymmetric supercapacitor possesses a pronounced energy density of 50.8 Wh kg −1 and remarkable cycling stability with a 4.3% deterioration of specific capacitance after 10 000 cycles. This work paves a new avenue to solve the two long‐standing significant challenges of MXene in the future. Abstract : A 3D porous oxidation‐resistant MXene/graphene composite is prepared through an efficient and fast self‐assembly route with the assistance of an in situ sacrificial metallic zinc template to suppress the oxidation and self‐restacking of MXene nanosheets. It exhibits excellent ambient stability, a striking specific capacitance of 393 F g –1, a superb rate performance (32.7% at 10 V s –1 ), and outstanding cycling stability.